Non-specific immunological effects of selected routine childhood immunisations: systematic review - Kandasamy, R; Voysey, M; McQuaid, F; de Nie, K; Ryan, R; Orr, O; Uhlig, U; Sande, C; O'Connor, D; Pollard, A (BMJ Publishing Group, 2016)
OBJECTIVE:  To identify and characterise non-specific immunological effects after routine childhood vaccines against BCG, measles, diphtheria, pertussis, and tetanus. DESIGN:  Systematic review of randomised controlled trials, cohort studies, and case-control studies. DATA SOURCES:  Embase, PubMed, Cochrane library, and Trip searched between 1947 and January 2014. Publications submitted by a panel of experts in the specialty were also included. ELIGIBILITY CRITERIA FOR SELECTING STUDIES:  All human studies reporting non-specific immunological effects after vaccination with standard childhood immunisations. Studies using recombinant vaccines, no vaccine at all, or reporting only vaccine specific outcomes were excluded. The primary aim was to systematically identify, assemble, and review all available studies and data on the possible non-specific or heterologous immunological effects of BCG; measles; mumps, measles, and rubella (MMR); diphtheria; tetanus; and pertussis vaccines. RESULTS:  The initial search yielded 11 168 references; 77 manuscripts met the inclusion criteria for data analysis. In most included studies (48%) BCG was the vaccine intervention. The final time point of outcome measurement was primarily performed (70%) between one and 12 months after vaccination. There was a high risk of bias in the included studies, with no single study rated low risk across all assessment criteria. A total of 143 different immunological variables were reported, which, in conjunction with differences in measurement units and summary statistics, created a high number of combinations thus precluding any meta-analysis. Studies that compared BCG vaccinated with unvaccinated groups showed a trend towards increased IFN-γ production in vitro in the vaccinated groups. Increases were also observed for IFN-γ measured after BCG vaccination in response to in vitro stimulation with microbial antigens from Candida albicans, tetanus toxoid, Staphylococcus aureas, lipopolysaccharide, and hepatitis B. Cohort studies of measles vaccination showed an increase in lymphoproliferation to microbial antigens from tetanus toxoid and C albicans Increases in immunogenicity to heterologous antigens were noted after diphtheria-tetanus (herpes simplex virus and polio antibody titres) and diphtheria-tetanus-pertussis (pneumococcus serotype 14 and polio neutralising responses) vaccination. CONCLUSIONS:  The papers reporting non-specific immunological effects had heterogeneous study designs and could not be conventionally meta-analysed, providing a low level of evidence quality. Some studies, such as BCG vaccine studies examining in vitro IFN-γ responses and measles vaccine studies examining lymphoproliferation to microbial antigen stimulation, showed a consistent direction of effect suggestive of non-specific immunological effects. The quality of the evidence, however, does not provide confidence in the nature, magnitude, or timing of non-specific immunological effects after vaccination with BCG, diphtheria, pertussis, tetanus, or measles containing vaccines nor the clinical importance of the findings.